Targeting Tumour-Associated Fibroblasts in Cancers - Shah, Kairav; Mallik, Sanchari Basu; Gupta, Praveer; Iyer, Abishek (Frontiers in Oncology, 2022)
Tumours develop within complex tissue environments consisting of aberrant oncogenic cancer cells, diverse innate and adaptive immune cells, along with structural stromal cells, extracellular matrix and vascular networks, and many other cellular and non-cellular soluble constituents. Understanding the heterogeneity and the complex interplay between these cells remains a key barrier in treating tumours and cancers. The immune status of the pre-tumour and tumour milieu can dictate if the tumour microenvironment (TME) supports either a pro-malignancy or an anti-malignancy phenotype. Identification of the factors and cell types that regulate the dysfunction of the TME is crucial in order to understand and modulate the immune status of tumours. Among these cell types, tumour-associated fibroblasts are emerging as a major component of the TME that is often correlated with poor prognosis and therapy resistance, including immunotherapies. Thus, a deeper understanding of the complex roles of tumour-associated fibroblasts in regulating tumour immunity and cancer therapy could provide new insight into targeting the TME in various human cancers. In this review, we summarize recent studies investigating the role of immune and key stromal cells in regulating the immune status of the TME and discuss the therapeutic potential of targeting stromal cells especially tumour-associated fibroblasts within the TME as an adjuvant therapy to sensitize immunosuppressive tumours and prevent cancer progression, chemo-resistance and metastasis.